Managing human resources: personnel management in transition. 4th ed. - Bach, Stephen E. (Oxford, 2005)
"Recent years have seen numerous appropriations of Thomas Aquinas’s work by a range of theologians, from liberal Catholics to the creators of radical orthodoxy. Responding to this upsurge of interest, this book goes straight to the heart of the contemporary debates about Thomism.